2016
DOI: 10.1016/j.msea.2015.10.082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of process parameters on microstructure and mechanical behaviors of friction stir linear welded aluminum to magnesium

Abstract: The microstructure and lap-shear behaviors of friction stir linear welded wrought Al alloy AA6022-T4 to cast Mg alloy AM60B joints were examined. A process window was developed to initially identify the potential process conditions. Multitudes of welds were produced by varying the tool rotation rate and tool traverse speed. Welds produced at 1500 revolutions per minute (rpm) tool rotation rate and either 50 mm/min or 75 mm/min tool traverse speed displayed the highest quasi-static failure load of ~3.3 kN per 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 36 publications
0
23
0
1
Order By: Relevance
“…Therefore, great efforts have been devoted to improve the joint performance. It was found that welding parameters such as weld speed and rotation rate can control heat input and modify grain size and texture of an FSW joint (Commin et al, 2009;Padmanaban et al, 2010;Yang et al, 2010Yang et al, , 2013Liu et al, 2011;Chowdhury et al, 2013;Hütsch et al, 2014;Pan et al, 2016;Rao et al, 2016;Alireza Askariani et al, 2017;Richmire et al, 2018). So, it is possible to improve the joint strength by varying welding parameters.…”
Section: Ways To Improve the Joint Strengthmentioning
confidence: 99%
“…Therefore, great efforts have been devoted to improve the joint performance. It was found that welding parameters such as weld speed and rotation rate can control heat input and modify grain size and texture of an FSW joint (Commin et al, 2009;Padmanaban et al, 2010;Yang et al, 2010Yang et al, , 2013Liu et al, 2011;Chowdhury et al, 2013;Hütsch et al, 2014;Pan et al, 2016;Rao et al, 2016;Alireza Askariani et al, 2017;Richmire et al, 2018). So, it is possible to improve the joint strength by varying welding parameters.…”
Section: Ways To Improve the Joint Strengthmentioning
confidence: 99%
“…These approaches can be achieved by optimizing the welding machine parameters, such as rotating velocity and welding speed. Rao et al stated that the tensile shear load of dissimilar 6022‐T4 Al/AM60B Mg friction stir lap welding (FSLW) joint was significantly affected by the rotating velocity and welding speed, and it was difficult to obtain a high‐quality joint under the parameters combination of low rotating velocity and high welding speed. Although a joint with relatively high quality can be obtained by directly optimizing the welding machine parameters, the problem of the narrow process parameters range for Al/Mg FSW process needs to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…The development of a perfect joining process between these metals is a decisive requirement to achieve a good combination of the characteristics of Mg and Al alloys. Therefore, solid state methods, as an alternative technology for joining Al and Mg, are of great interest [9,10].…”
Section: Introductionmentioning
confidence: 99%